Control de las cuentas por cobrar de la comercializadora Agrícola “Comagrico S.A.” de la ciudad de Babahoyo de los períodos 2021 – 2022 - Pazmiño Martínez, Pablo Xavier (2023)
In this case study, the management of accounts receivable at Agricultural Marketing Company COMAGRICO S.A. during the periods 2021-2022 was addressed. A fundamental issue related to the increase in these accounts at the end of each period was identified. This concerning trend posed a significant challenge in the company's financial decision-making, prompting the conduct of this research. The justification lies in the critical importance of accounts receivable management for the financial health and liquidity of the company, as well as its influence on strategic decision-making. The general objective focused on a comprehensive analysis of the control of these accounts, evaluating their impact on the company's liquidity and their recovery processes, with the purpose of identifying internal weaknesses and areas for improvement. The methodology employed was mixed, including the analysis of financial data from the balance sheets and comprehensive income statements, as well as conducting interviews with the company's accountant to gather qualitative information about the collection processes and their challenges. This study underscored the critical need to enhance accounts receivable management at COMAGRICO S.A. to ensure a healthy cash flow and solid financial decision-making. It is recommended to review and strengthen credit evaluation processes, implement more effective collection strategies, and maintain rigorous tracking of outstanding accounts.